Independent Commissioners as Gatekeepers: Influences on Debt Policies and Ownership in Coal Mining Firms - Siti Nurjanah, Novia; Valdiansyah, Riyan (Universitas Nahdlatul Ulama Surabaya, 2025)
This study analyzes the role of governance mechanisms in moderating the effect of share ownership status (managerial and institutional) on debt policy in coal mining companies in Indonesia for the 2019-2023 period. Utilizing secondary data from 13 companies (65 company-years) and employing the panel regression method with EViews 13 tools, the study's findings are as follows: Firstly, managerial ownership has been found to exert a significant positive influence on debt policy, as indicated by the Debt-to-Equity Ratio (DER). Secondly, institutional ownership has been demonstrated to possess a substantial negative effect, reflecting investors' propensity for a conservative capital structure. Thirdly, the presence of independent commissioners has been observed to diminish the positive effect of managerial ownership, underscoring the significance of supervision in balancing risk. Finally, independent commissioners have been found to mitigate the negative effect of institutional ownership, highlighting the importance of transparency. The study's findings offer guidance for various stakeholders, including management, investors, and regulators, in financial decision-making and the implementation of Good Corporate Governance. The study's limitations stem from its narrow focus on the coal mining subsector and the exclusion of additional variables, such as profitability. Suggestions for future research include expanding the study to include additional sectors and incorporating contextual variables.